Impact of Participatory Decision Making on Organisational Goal Attainment (International Journal of Business, Economics and Management, 2019)
The study centred on participatory decision making and organizational goal attainment. This study investigated the extent to which participative decision making affects the organizational goal attainment. The study had a sample size of 136 obtained using the Cochran statistical formula. The study employed a survey research design. The instrument used for data collection was the questionnaire. The data from the responses were presented in frequencies, simple percentages. Three hypotheses were tested using the chi-square X2 and t-test statistical tools. The study found out that: Employee participation in decision making significantly improves job productivity (X2 cal = 2.554 > X2 0.5 = 0.6763); employee participation in decision, making relates to employee motivation (Fc – test = 21 .56 > ft 1 = 2.01); the policy of employee participation in decision-making is significant in organizational goal attainment (X2 Cal = 1.887 > X2 0.5 = 0.6763) The study, based on the above findings, concluded that for the goal attainment of any organization to be achieved successfully depended on the extent to which the organization integrated the workers into the policy formulation and implementation. The study recommends that organizations should adopt the ring show management theory as a way of survival.